2005
DOI: 10.1111/j.1471-4159.2005.03337.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of creatine treatment on survival and differentiation of GABA‐ergic neurons in cultured striatal tissue

Abstract: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder, characterized by a prominent loss of GABA-ergic medium-sized spiny neurons in the caudate putamen. There is evidence that impaired energy metabolism contributes to neuronal death in HD. Creatine is an endogenous substrate for creatine kinases and thereby supports cellular ATP levels. This study investigated the effects of creatine supplementation (5 mM) on cell survival and neuronal differentiation in striatal cultures. Chronic crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 70 publications
6
40
1
3
Order By: Relevance
“…In vitro studies mimicking Parkinson's disease revealed that Cr has protective effects against neurotoxic insults (Andres et al 2005). A large RCT corroborated such promising observations, indicating that Cr supplementation is not futile in Parkinson's patients.…”
Section: Brain Disordersmentioning
confidence: 81%
“…In vitro studies mimicking Parkinson's disease revealed that Cr has protective effects against neurotoxic insults (Andres et al 2005). A large RCT corroborated such promising observations, indicating that Cr supplementation is not futile in Parkinson's patients.…”
Section: Brain Disordersmentioning
confidence: 81%
“…It is worth considering that GABA receptor activity plays an important role during brain development, participating in neuron differentiation, migration, dendritic maturation, and modeling of neuronal circuitry (for an extensive review see Represa and Ben-Ari, 2005). Moreover, in vitro Cr supplementation has been observed to readdress neuron differentiation toward a GABA-ergic phenotype in striatal (Andres et al, 2005) and spinal cord (Ducray et al, 2007) cell cultures.…”
mentioning
confidence: 98%
“…23 In cultured cells, creatine supplementation protects rat hippocampal neurons against glutamate and amyloid β-peptide toxicity. 24 Data using human fetal striatal and mesencephalic tissue identified creatine as a potent natural survival and neuroprotective factor for γ-aminobutyric acid-ergic neurons in a model for Huntington disease 25 and of dopaminergic neurons in a model for Parkinson disease. 26 Recent interest in routine screening children with ASD for inborn errors of metabolism, and in particular CDS, 27,28 raises the question of how many children with ASD could potentially benefit from such screening.…”
Section: What This Study Addsmentioning
confidence: 99%